Gross, Histological and Histochemical Observations on the Gland of Third Eyelid in Buffalo Calf (Bubalus bubalis) - Verma, Abhinov (Indian Journal of Veterinary Anatomy, 2019)
The present study was conducted on 10 male buffalo calves of non-descript breed having 1-2 year of age. The gland of third eyelid was located at medial canthus of eye. It was consisted of two parts viz: superficial or cartilaginous part or nictitans gland and deep or non cartilaginous part or harderian gland. The gland was compound tubuloalveolar type and mixed in nature. The capsule of the gland was rich in collagen and reticular fibres. The reticular fibres supported the basement membrane of epithelium of all acini. Myoepithelial cells wereobserved between basement membrane and nucleus of acinar cells. The acinar cell cytoplasm, basement membrane and ductular epithelium showed strong periodic acid schiff reaction. Mucous acini showed strong reaction to acid mucopolysaccharide while serous acini were poorly stained with acid mucopolysaccharide. Bound lipids were observed in the basement membrane of acinar epithelium. In cartilaginous part the hyaline cartilage had lacunae filled with one or two chondrocytes; some chondrocytes were in dividing stage. The collagen fibres were observed in perichondrium of cartilage.